Empowering the Fatayat NU’s Group in Karimunjawa Village Through IoT-Based Hydroponic - Junvidya Heroweti (Sekolah Vokasi Universitas Diponegoro, 2025)
[Title: Empowering the Fatayat NU’s Group in Karimunjawa Village Through IoT-Based Hydroponic] Karimunjawa Village, located on Karimunjawa Island in Central Java, faces persistent food security issues due to geographical geographic isolation, limited agricultural area, and dependence on imported vegetables from Jepara at considerably elevated rates. Extreme weather causes transportation disruptions, leading to significant vegetable shortages. This community empowerment initiative concentrated on the Fatayat NU’s Group. The intervention by combining hydroponic vegetable cultivation with Internet of Things (IoT) technology. Activities included institutional strengthening, training on hydroponic systems, IoT-based monitoring for optimum water.The program facilitated access to hydroponic equipment, IoT devices, and vegetable seeds by providing structured training and mentoring. Fatayat NU's organizational capacity was improved, its members' technical skills in sustainable cultivation were improved, and the awareness of balanced nutrition was promoted. In turn, the implementation of IoT ensured a more consistent local vegetable production by reducing water consumption by 30% and the duration of the harvesting process.In conclusion, the sustainable approach of empowering groups via IoT-based hydroponic farming offers a method to bolster economic resilience, and fortify food security in island communities such as Karimunjawa.